The testicular transcriptome associated with spermatogonia differentiation initiated by gonadotrophin stimulation in the juvenile rhesus monkey (Macaca mulatta). Issue 10 (30th August 2017) - Ramaswamy, Suresh; Walker, William H.; Aliberti, Paula; Sethi, Rahil; Marshall, Gary R.; Smith, Alyxzandria; Nourashrafeddin, Seyedmehdi; Belgorosky, Alicia; Chandran, Uma R.; Hedger, Mark P.; Plant, Tony M.
Abstract: STUDY QUESTION: What is the genetic landscape within the testis of the juvenile rhesus monkey ( Macaca mulatta ) that underlies the decision of undifferentiated spermatogonia to commit to a pathway of differentiation when puberty is induced prematurely by exogenous LH and FSH stimulation? SUMMARY ANSWER: Forty-eight hours of gonadotrophin stimulation of the juvenile monkey testis resulted in the appearance of differentiating B spermatogonia and the emergence of 1362 up-regulated and 225 down-regulated testicular mRNAs encoding a complex network of proteins ranging from enzymes regulating Leydig cell steroidogenesis to membrane receptors, and from juxtacrine and paracrine factors to transcriptional factors governing spermatogonial stem cell fate. WHAT IS KNOWN ALREADY: Our understanding of the cell and molecular biology underlying the fate of undifferentiated spermatogonia is based largely on studies of rodents, particularly of mice, but in the case of primates very little is known. The present study represents the first attempt to comprehensively address this question in a highly evolved primate. STUDY DESIGN, SIZE, DURATION: Global gene expression in the testis from juvenile rhesus monkeys that had been stimulated with recombinant monkey LH and FSH for 48 h ( N = 3) or 96 h ( N = 4) was compared to that from vehicle treated animals ( N = 3). Testicular cell types and testosterone secretion were also monitored. PARTICIPANTS/MATERIALS, SETTING, METHODS: Precocious testicular puberty was initiated in juvenile rhesus monkeys, 14–24 months of age, using a physiologic mode of intermittent stimulation with i.v. recombinant monkey LH and FSH that within 48 h produced 'adult' levels of circulating LH, FSH and testosterone. Mitotic activity was monitored by immunohistochemical assays of 5-bromo-2′-deoxyuridine and 5-ethynyl-2′-deoxyuridine incorporation. Animals were bilaterally castrated and RNA was extracted from the right testis. Global gene expression was determined using RNA-Seq. Differentially expressed genes (DEGs) were identified and evaluated by pathway analysis. mRNAs of particular interest were also quantitated using quantitative RT-PCR. Fractions of the left testis were used for histochemistry or immunoflouresence. MAIN RESULTS AND THE ROLE OF CHANCE: Differentiating type B spematogonia were observed after both 48 and 96 h of gonadotrophin stimulation. Pathway analysis identified five super categories of over-represented DEGs. Repression of GFRA1 ( glial cell line-derived neurotrophic factor family receptor alpha 1) and NANOS2 (nanos C2HC-type zinc finger 2) that favor spermatogonial stem cell renewal was noted after 48 and 96 h of LH and FSH stimulation. Additionally, changes in expression of numerous genes involved in regulating the Notch pathway, cell adhesion, structural plasticity and modulating the immune system were observed. Induction of genes associated with the differentiation of spermatogonia stem cells ( SOHLH1 (spermatogenesis- and oogenesis-specific basic helix-loop-helix 1), SOHLH2 and KIT (V-Kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog)) was not observed. Expression of the gene encoding STRA8 (stimulated by retinoic acid 8), a protein generally considered to mark activation of retinoic acid signaling, was below our limit of detection. LARGE SCALE DATA: The entire mRNA data set for vehicle and gonadotrophin treated animals ( N = 10) has been deposited in the GEO-NCBI repository (GSE97786). LIMITATIONS REASONS FOR CAUTION: The limited number of monkeys per group and the dilution of low abundance germ cell transcripts by mRNAs contributed from somatic cells likely resulted in an underestimation of the number of differentially expressed germ cell genes. WIDER IMPLICATIONS OF THE FINDINGS: The findings that expression of GDNF (a major promoter of spermatogonial stem cell renewal) was not detected in the control juvenile testes, expression of SOHLH1, SOHLH2 and KIT, promoters of spermatogonial differentiation in mice, were not up-regulated in association with the gonadotrophin-induced generation of differentiating spermatogonia, and that robust activation of the retinoic acid signaling pathway was not observed, could not have been predicted. These unexpected results underline the importance of non-human primate models in translating data derived from animal research to the human situation. STUDY FUNDING/COMPETING INTEREST(S): The work described was funded by NIH grant R01 HD072189 to T.M.P. P.A. was supported by an Endocrine Society Summer Research Fellowship Award and CONICET (Argentine Research Council), S.N. by a grant from Vali-e-Asr Reproductive Health Research Center of Tehran University of Medical Sciences (grant #24335-39-92) to Dr Batool Hosseini Rashidi, and M.P.H. by grants from the National Health and Medical Research Council of Australia, and the Victorian State Government's Operational Infrastructure Support Program. The authors have nothing to disclose.